(untitled) (Research, Society and Development, 2022)
The objective of this work was to evaluate the influence of two leaf removal managements on the viticultural performance of the Marselan variety cultivated under plastic cover in Nova Trento - SC. The experiment was evaluated during the 2020/2021 and 2021/2022 seasons. The variety Marselan (Vitis vinifera L.) was grafted on Gravesac rootstock and implanted in 2018 under Y-trellis training system with 3.0 m x 1.5 m spacing. The plastic cover used is made of low density polyethylene (LDPE). The treatments consisted of partial leaf removal of basal leaves close to the clusters with the maintenance of lateral shoots and partial leaf removal of basal leaves with total removal of lateral shoots. The experimental design was randomized blocks, with four blocks and five plants per replication. The parameters were number of shoots (n° shoots plant-¹), total leaf area per shoot (m² branch-¹), leaf area per plant (m² plant-¹), leaf area per hectare (m² ha- ¹), Leaf Area:Production ratio (m² Kg-¹). At harvest, plant production (Kg plant-¹), estimated yield (t ha-¹), fertility index, cluster length (cm), cluster weight (g), weight of 50 berries (g), number of berries per cluster, compactness index, berry diameter (mm), soluble solids (°Brix), pH and total acidity (mEq L-¹). The leaf area resulting from the treatment without secondary shoots was lower than expected to maintain the vegeto productive balance. The treatments did not influence the productive parameters and both showed adequate results for the elaboration of quality wines.